Behavioural supports for students with autism spectrum disorders: practice, policy, and implications for special education reform in China. Issue 1 (2nd January 2022) - Han, Chen; Cumming, Therese M.
ABSTRACT: The educational inclusion of children with Autism Spectrum Disorder (ASD) can be challenging, due to behavioural issues. Scant research has been conducted to investigate behavioural interventions for students with ASD in the Chinese context. Since special education in China varies greatly from that in western countries such as Australia, particularly in the area of the effective application of evidence-based practices, this must be a priority for researchers and teachers alike. The current study employed a literature review to identify effective practices to support the acquisition of appropriate behaviours of children with autism in different educational environments and contexts. These findings were then used in combination with an analysis of international, Australian, and Chinese policies to make suggestions and recommendations for special education reform in China. Results suggest that antecedent interventions, Functional Behaviour Assessment (FBA), social stories, and teaching self-management are the four most effective practices to decrease the challenging behaviours of students with ASD. Suggestions for further research and policy reform are provided.